The Relationship Between Social Media Use And Mental Health Problems Affecting Adolescents In Public Health Center X, Cirebon Regency - Khusana Rahma; ‎ Amalia; Ricky Riyanto Iksan (STIKes RSPAD RSPAD Gatot Soebroto, 2026)
The development of digital technology has significantly increased social media use among adolescents. High levels of use have the potential to impact psychological conditions, such as depression, anxiety, and sleep disorders. In Indonesia, increased internet access among adolescents also increases the risk of exposure to digital content that impacts mental health. A preliminary study at the Lurah Community Health Center (Puskesmas Lurah) showed that some adolescents experience difficulty controlling their social media use, which impacts anxiety and sleep patterns. Objective: To determine the relationship between social media use and mental health problems among adolescents in the working area ofPuskesmas X. Methods: This quantitative study used a correlational design and a cross-sectional approach. The population was 409 adolescents aged 15–19 years, with a sample of 80 respondents selected using simple random sampling. Primary data were collected through questionnaires and analyzed using the Chi-Square test. Results: In the mild social media use category, most respondents were in normal condition (58%). In the moderate category, the majority experienced mental health problems (75%), and in the severe category, almost all respondents experienced mental health problems (90%). The Chi-Square test results showed a p-value of 0.010 (p < 0.05), indicating a significant relationship between social media use and mental health problems. Conclusion: The higher the level of social media use, the greater the proportion of adolescents experiencing mental health problems.